Revisiting What Constitutes a Neglected Tropical Disease? - Paul J Brindley; Peter J Hotez; Shaden Kamhawi (PLoS Neglected Tropical Diseases)
PLOS Neglected Tropical Diseases (PLOS NTDs) publishes research devoted to pathogenesis and other clinical aspects, epidemiology, prevention, diagnosis, treatment, and control of the neglected tropical diseases (NTDs), as well as work relevant to public health policy. We define NTDs as poverty-promoting infectious diseases that can negatively impact the quality of life in rural areas and poor urban areas of low- and middle-income countries but which can also affect specific communities within high-income countries. The poverty-inducing effects of the NTDs operate by impairing child health and development, pregnancy outcomes for both mother and child, worker productivity, and quality of life. The NTDs also exhibit stigmatizing features, impeditive to equity and economic stability. The objective of this editorial is to provide an update on the conditions that PLOS NTDs will consider for publication.